1996
DOI: 10.1074/jbc.271.40.24425
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Upstream Activation Sequence and Two Rox1p-responsive Sites Controlling the Induction of the Yeast HEM13 Gene by Oxygen and Heme Deficiency

Abstract: The Saccharomyces cerevisiae HEM13 gene codes for coproporphyrinogen oxidase, an oxygen-requiring enzyme catalyzing the sixth step of heme biosynthesis. Its transcription has been shown to be induced 40 -50-fold in response to oxygen or heme deficiency, in part through relief of repression exerted by Rox1p and in part by activation mediated by an upstream activation sequence (UAS). This report describes an analysis of HEM13 UAS and of the Rox1p-responsive sites by electrophoretic mobility shift assays, DNase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Still, salt or water addition sufficed to briefly repress HEM13 (Fig. 5A), a known oxygen-repressed gene (2). We conclude that the expression of this set of genes is exquisitely sensitive to addition of even trace amounts of oxygen.…”
Section: Resultsmentioning
confidence: 87%
“…Still, salt or water addition sufficed to briefly repress HEM13 (Fig. 5A), a known oxygen-repressed gene (2). We conclude that the expression of this set of genes is exquisitely sensitive to addition of even trace amounts of oxygen.…”
Section: Resultsmentioning
confidence: 87%
“…CPO encodes the enzyme coproporphyrinogen oxidase that catalyzes the sixth step in the heme biosynthetic pathway. Its transcription was induced 40-50-fold under conditions of oxygen or heme deficiency (Amillet et al, 1996;Blanco et al, 2005). Previous works have also shown that coproporphyrinogen oxidase activity became rate-limiting for heme production when its substrate oxygen is limiting.…”
Section: Discussionmentioning
confidence: 95%
“…Previous works have also shown that coproporphyrinogen oxidase activity became rate-limiting for heme production when its substrate oxygen is limiting. Cells responded to oxygen limitation by increasing the amount of the enzyme (Amillet et al, 1996;Blanco et al, 2005). Hence, coproporphyrinogen oxidase may play a crucial role in linking heme synthesis to the oxygen/heme-dependent control of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Transcript levels of HEM13, the rate-limiting step of heme biosynthesis (57), were reduced in response to seven drug treatments and, again, in none of the deletion strains. HEM13 is repressed by heme and oxygen (1,22), raising the possibility that levels of one or both are elevated following treatment. This is consistent with the hypothesis of increased intracellular oxygen suggested by the responses of anaerobiosis-induced and oxygen stress genes described above.…”
Section: Erg12 Are2 Coq7 [Also Referred To As Cat5] Far3 Fig1 Hementioning
confidence: 99%